College of William and Mary records - College of William and Mary.
Correspondence, administrative papers, financial records, and miscellaneous writings consisting chiefly of lectures, sermons, and poetry. Includes material relating to faculty appointments and fundraising for reconstruction of buildings damaged during the Civil War; and a questionnaire completed by Woodrow Wilson relating to his duties as president of Princeton University. Persons represented include Henry Ward Beecher, James Blair, William and Thomas Dawson, Benjamin S. Ewell, Joseph Henry, George F. Hoar, Thomas Jefferson, John Johns, Robert McCandlish, Bishop James Madison, George Meade, Sir John Randolph, and St. George Tucker.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Collection material in English, with Latin, and Greek.
Keywords: Beecher, Henry Ward, -- 1813-1887.; Blair, James, -- 1656-1743.; Dawson, Thomas, -- -1761.; Dawson, William, -- 1705?-1752.; Ewell, Benjamin Stoddert, -- 1810-1894; Henry, Joseph, -- 1797-1878.; Hoar, George Frisbie, -- 1826-1904.; Jefferson, Thomas, -- 1743-1826.; Johns, J. -- 1796-1876.; Madison, James, -- 1749-1812.; McCandlish, Robert; Meade, George Gordon, -- 1815-1872.; Randolph, John, -- Sir, -- approximately 1693-1737.; Tucker, St. George, -- 1752-1827.; Wilson, Woodrow, -- 1856-1924.; Princeton University; American poetry; Education; Sermons, American; Universities and colleges -- New Jersey; Universities and colleges -- Virginia; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; Williamsburg (Va.) -- History